Tibial plateau fracture related to unicompartmental knee arthroplasty: Two case reports and literature review - Lu, Chao (Medicine (Baltimore), 2019)
RATIONALE: Unicompartmental knee arthroplasty (UKA) is an effective method to treat single compartment disease of the knee joint. Report about the complications of UKA, especially tibial plateau fractures, is rare. Given its rarity, its pathogenesis is not well described, and a standard of treatment is still not established. Therefore, relevant studies and analysis of this complication have a significant effect on helping physicians avoid risks and guide clinical diagnosis and treatment. PATIENT CONCERNS: The 1st case corresponds to a 70-year-old male patient who complained of knee pain, difficulty walking, nocturnal rest pain, and elevated skin temperature at 3 weeks after the left knee arthroplasty. The second case is a 72-year-old female patient who complained of left knee pain and swelling during movement at 2 weeks after the left knee arthroplasty. DIAGNOSIS: The 1st case showed a fracture of the medial malleolus of the left knee and a secondary depression of the medial tibial plateau in X-rays and the second case showed a fracture of the medial malleolus of the left knee in computed tomography (CT) and X-rays. INTERVENTIONS: The 1st case was treated with plate and screw fixation and the second case was treated conservatively and immobilized using brace and remained nonweight bearing for 6 weeks. OUTCOMES: After 1 year, both patients have good joint activity, and there was no pain or loosening of the prosthesis and fragment displacement. LESSONS: The incidence of tibial plateau fractures (TPF) related to UKA might be low, but fatal and difficult to treat. Its pathogenesis determines procedure-related factors; when fracture develops, treatment should be based on the degree of displacement, stability of implant fixation, etc.